SERS‐based assays for sensitive detection of modafinil. (27th May 2015) - Caglayan, Mehmet Gokhan; Torul, Hilal; Onur, Feyyaz; Tamer, Ugur
Abstract : In this paper, we proposed two sensitive surface‐enhanced Raman spectroscopy assays for the determination of modafinil in urine matrix. In the first assay, modafinil was extracted by solid phase extraction and determined after sandwiching with silver nanoparticles. In the second assay, modafinil was extracted by non‐specific interaction with magnetic gold nanoparticles and determined by sandwiching with magnetic gold and silver nanoparticles. The non‐specific magnetic extraction does not require any analyte specific agent like antibody, aptamer, or molecularly imprinted polymer, therefore, the cost and complexity of the assay is very low. Both assays are capable for application to urine samples with the detection limits under the minimum required performance limit of modafinil. The assays were validated in terms of accuracy, precision, detection limits, and ranges. Copyright © 2015 John Wiley & Sons, Ltd. Abstract : Modafinil is one of the prohibited substances in sport. Surface‐enhanced Raman spectroscopy‐based assays were developed for the fast and sensitive detection of modafinil in urine matrix by using hybrid magnetic nanoparticles as magnetic separation agent. The performances of solid phase extraction and magnetic separation were compared after sandwiching with silver nanoparticles.